2012
DOI: 10.9790/3013-0230525533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aluminium Chloride Exposure on the Histology of the Liver of Adult Wistar Rats

Abstract: ABSTRACT:Aluminium is presents in many manufactured foods, medicines and is also added to drinking water for purification purposes. It presence has so heavily contaminated the environment that exposure to it is virtually inescapable. The liver is the largest gland of the body that processes blood and breaks down nutrients, drugs into forms that are easier to use for the rest of the body. This study was aimed at evaluating the possible effects that aluminium chloride exposure could have on the histology of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
5
10
0
Order By: Relevance
“…In addition to periportal fibroplasia, edema, biliary hyperplasia with infiltration of inflammatory cells and hepatocytic vaculation. The current hepatic lesions were parallel to those reported by Kutlubay et al (2007), El-Sayed (2011), Buraimoh et al (2012), Goma andTohamy (2016) andoda (2016). Aluminum nephrotoxicity can occur when the urinary bladder is irrigated with 1% alum to treat bladder hemorrhage so it occurs in patients who have renal insufficiency Phelps et al (1999).…”
Section: Figure (1)supporting
confidence: 69%
“…In addition to periportal fibroplasia, edema, biliary hyperplasia with infiltration of inflammatory cells and hepatocytic vaculation. The current hepatic lesions were parallel to those reported by Kutlubay et al (2007), El-Sayed (2011), Buraimoh et al (2012), Goma andTohamy (2016) andoda (2016). Aluminum nephrotoxicity can occur when the urinary bladder is irrigated with 1% alum to treat bladder hemorrhage so it occurs in patients who have renal insufficiency Phelps et al (1999).…”
Section: Figure (1)supporting
confidence: 69%
“…However, epidemiological studies have indicated a link between Al in drinking water and AD and a variety of human and animal studies have implicated learning and memory deficits after Al exposure. (Buraimoh et al, 2011a;Exley, 2005;Yokel, 2000).It was also postulated by Buraimoh et al, 2011b: that Aluminium chloride exposure has negative effects on behaviour of adult wistar rats (i.e. alter behaviour).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the beneficial effect of Allium cepa on arsenic acid induced-and cadmium-induced hepatic damage in rats [5][6][7]26]. Exposure of human beings to both Allium cepa and aluminum chloride is insurmountable [2].…”
Section: Discussionmentioning
confidence: 99%
“…During normal breathing, at least 1.4 µg of aluminum in particulate was reported to be inhaled per day [3]. With a significant aluminum load, the excretory capacity of the kidney is exceeded leading to deposition of the minerals in various tissues including the liver and consequently resulting in hepatotoxicity [2,4,5].…”
Section: Introductionmentioning
confidence: 99%